Global solutions and self‐similar solutions for coupled nonlinear Schrödinger equations. (1st February 2017) - Ye, Yaojun
Abstract : In this paper, we prove the existence and uniqueness for the global solutions of Cauchy problem for coupled nonlinear Schrödinger equations and obtain the continuous dependence result on the initial data and the stronger decay estimate of global solutions. In particular, we show the existence and uniqueness of self‐similar solutions. Also, we build some asymptotically self‐similar solutions. Copyright © 2017 John Wiley & Sons, Ltd.